Find the product of 0.2xy(3x+2y) and verify the result when x=5 and y= -1.
Answers
The product for the given expression is ![0.2xy(3x+2y)=0.6x^2y+0.4xy^2 0.2xy(3x+2y)=0.6x^2y+0.4xy^2](https://tex.z-dn.net/?f=0.2xy%283x%2B2y%29%3D0.6x%5E2y%2B0.4xy%5E2)
The result
when x=5 and y=-1 is -13
Step-by-step explanation:
Given expression is 0.2xy(3x+2y)
To find the given product of the expression and verify the result when x=5 and y=-1 :
- 0.2xy(3x+2y)
- =0.2xy(3x)+0.2xy(2y)
- Therefore 0.2xy(3x+2y)
The product for the given expression is ![0.2xy(3x+2y)=0.6x^2y+0.4xy^2 0.2xy(3x+2y)=0.6x^2y+0.4xy^2](https://tex.z-dn.net/?f=0.2xy%283x%2B2y%29%3D0.6x%5E2y%2B0.4xy%5E2)
Now verify the result when x=5 and y=-1 :
- Put x=5 and y=-1 in the above expression we get
The result
when x=5 and y=-1 is -13
Answer:
The product for the given expression is 0.2xy(3x+2y)=0.6x^2y+0.4xy^20.2xy(3x+2y)=0.6x
2
y+0.4xy
2
The result 0.6x^2y+0.4xy^20.6x
2
y+0.4xy
2
when x=5 and y=-1 is -13
Step-by-step explanation:
Given expression is 0.2xy(3x+2y)
To find the given product of the expression and verify the result when x=5 and y=-1 :
0.2xy(3x+2y)
=0.2xy(3x)+0.2xy(2y)
=0.6x^2y+0.4xy^2=0.6x
2
y+0.4xy
2
Therefore 0.2xy(3x+2y)=0.6x^2y+0.4xy^2=0.6x
2
y+0.4xy
2
The product for the given expression is 0.2xy(3x+2y)=0.6x^2y+0.4xy^20.2xy(3x+2y)=0.6x
2
y+0.4xy
2
Now verify the result when x=5 and y=-1 :
0.6x^2y+0.4xy^20.6x
2
y+0.4xy
2
Put x=5 and y=-1 in the above expression we get
=0.6(5)^2(-1)+0.4(5)(-1)^2=0.6(5)
2
(−1)+0.4(5)(−1)
2
=-0.6(25)+0.4(5)=−0.6(25)+0.4(5)
=-15+2=−15+2
=-13=−13
The result 0.6x^2y+0.4xy^20.6x
2
y+0.4xy
2
when x=5 and y=-1 is -13